2021
DOI: 10.1371/journal.pbio.3001006
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 variants reveal features critical for replication in primary human cells

Abstract: Since entering the human population, Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2; the causative agent of Coronavirus Disease 2019 [COVID-19]) has spread worldwide, causing >100 million infections and >2 million deaths. While large-scale sequencing efforts have identified numerous genetic variants in SARS-CoV-2 during its circulation, it remains largely unclear whether many of these changes impact adaptation, replication, or transmission of the virus. Here, we characterized 14 different lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 67 publications
1
44
0
1
Order By: Relevance
“…Upon reaching 70–80% confluence, 17 Cl-1 cells were infected with MHV-A59 at MOI 5 as described [ 9 ]. Vero CCL81 and Calu3 cells were infected with SARS-CoV-2 (SARS-CoV-2/human/Switzerland/ZH-UZH-IMV5/2020) at two MOIs (1 and 5) for 24 or 48 has previously described [ 107 , 108 ]. Caco2 cells were infected with SARS-CoV-2 (isolate hCoV-19/Edinburgh/2/2020, a kind gift from Dr Christine Tait-Burkhard and Dr Juergen Haas) at MOI 0.01 and incubated for 48 h in MEM containing 1% L-glutamine, 1% non-essential aminoacids, 1% penicillin/streptomycin and supplemented with 2% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…Upon reaching 70–80% confluence, 17 Cl-1 cells were infected with MHV-A59 at MOI 5 as described [ 9 ]. Vero CCL81 and Calu3 cells were infected with SARS-CoV-2 (SARS-CoV-2/human/Switzerland/ZH-UZH-IMV5/2020) at two MOIs (1 and 5) for 24 or 48 has previously described [ 107 , 108 ]. Caco2 cells were infected with SARS-CoV-2 (isolate hCoV-19/Edinburgh/2/2020, a kind gift from Dr Christine Tait-Burkhard and Dr Juergen Haas) at MOI 0.01 and incubated for 48 h in MEM containing 1% L-glutamine, 1% non-essential aminoacids, 1% penicillin/streptomycin and supplemented with 2% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…It was suggested that the acquisition of the furin-cleavage site in the SARS-CoV-2 S protein was essential for zoonotic transfer to humans 9,163 , and experimental data confirmed that SARS-CoV-2 pseudoviruses lacking this cleavage site in the S protein are incapable of facilitating entry into human airway cells 9 . Notably, the furin site is not essential for infection of mammalian epithelial cells generally, as it is lost after a few passages of the virus in Vero cells (African green monkey kidney epithelial cells) 28,[164][165][166][167] . However, recent preliminary studies show virus passage in TMPRSS2overexpressing Vero cells or in human lung cells prevents deletion or mutation of this site [167][168][169] .…”
Section: S Proteins From Sarbecoviruses In Reservoir Speciesmentioning
confidence: 99%
“…Most mutations are neutral or detrimental to virus fitness, while some may provide selective advantages, such as increased infectivity, transmissibility and reduced effectiveness of the immune response. There have been thousands of mutations recorded so far in SARS-CoV-2, with D614G being the most common mutation: it is found in a high number of isolates worldwide and has been suggested to increase replication and human-to-human transmission [ 96 , 97 , 98 ]. D614G enhances viral replication by increasing the stability of virions in human lung epithelial cells and airway tissues [ 99 ].…”
Section: Transmissibility and Immune Evasion Of Sars-cov-2mentioning
confidence: 99%